Highly reconstructed Ni-doped glassy MOFs electrocatalyst and preparation method and application thereof

By introducing Ni metal particles into the electrocatalyst and using vitrification and electrochemical reconstruction techniques, an efficient glass MOFs catalyst was constructed, which solved the problems of low catalytic efficiency of existing electrocatalysts and difficult to process in powder state, and achieved excellent HMF electrooxidation performance and industrial application potential.

CN119465284AActive Publication Date: 2025-02-18XI AN JIAOTONG UNIV +1

Patent Information

Application Number
CN202411584314.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-02-18
Estimated Expiration
2044-11-07

AI Technical Summary

Technical Problem

The existing electrocatalysts have problems such as low catalytic efficiency, insufficient active sites, low electron transfer efficiency and difficult powder state processing, which limit their application in large-scale applications.

Method used

By introducing Ni metal particles, a new glassy MOFs catalyst is constructed, and vitrification and electrochemical reconstruction techniques are used to improve the active site and charge transfer capability of the catalyst.

Benefits of technology

It achieves efficient HMF electrooxidation performance, and the catalyst has excellent reaction performance and industrial application potential, solving the problem of difficult processing of powder catalysts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119465284A_ABST
    Figure CN119465284A_ABST
Patent Text Reader

Abstract

The invention discloses a highly reconstructed Ni-doped glassy MOFs electrocatalyst and a preparation method and application thereof.The preparation method comprises the steps that a solution containing cobalt salt and an organic ligand is subjected to a hydrothermal reaction, and ZIF-Co powder is obtained; taking a mixture of ZIF-Co powder and a nickel source as a powder precursor; loading the powder precursor on the electrode material to obtain a catalyst-loaded electrode material; the electrode material loaded with the catalyst is vitrified through a melting quenching technology and then reconstructed, and the highly reconstructed Ni-doped glassy MOFs electrocatalyst is obtained. According to the method, electrochemical surface reconstruction is promoted by vitrification, the glassy MOFs catalyst with rich active sites is obtained, the problem that the active sites of the MOFs material are not easy to expose is solved, in addition, the glassy MOFs can be directly fused and attached to an electrode material without a binder, the problem that a powder catalyst is difficult to process is solved, and the preparation process is simple. And device assembly and industrial large-scale production are facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrocatalysis, and in particular relates to a highly reconstructed Ni-doped glassy MOFs electrocatalyst and a preparation method and application thereof. Background Art

[0002] 5-Hydroxymethylfurfural (HMF) is considered to be one of the most versatile biomass platform molecules, which can be used to derive a variety of high-value-added chemicals with important industrial applications. In particular, its oxidation product 2,5-furandicarboxylic acid (FDCA) has high commercial application value and can be used to manufacture many important polymer materials. It has a wide range of applications in engineering plastics, medicine, textiles and other fields. Traditional thermal catalytic oxidation of HMF mostly requires precious metal-based catalysts to achieve a FDCA yield of more than 90%, involving high reaction temperatures and relatively high oxygen pressures, as well as some expensive organic toxic reagents, which greatly limits the large-scale application of these systems. As an emerging FDCA preparation method, electrocatalytic oxidation is a "green" catalytic process that can selectively oxidize HMF to FDCA through anodic electrocatalytic oxidation at room temperature and pressure. This method uses electrode potential and current density as two additional controllable parameters to achieve adjustable substrate reactivity and high selectivity of target products. More importantly, the HMF oxidation reaction (HMFOR) can replace the oxygen evolution reaction (OER) with slow reaction kinetics and combine with the hydrogen evolution reaction (HER) to significantly improve the overall electrolysis efficiency and achieve the production of high-value chemicals.

[0003] It is particularly important to design catalysts with fast reaction kinetics, strong oxidation equilibrium ability and high selectivity. A large number of studies in recent years have shown that Co / Ni-based metal organic frameworks (MOFs) have great potential in the field of electrocatalysis due to their diversity in structure and morphology, fast kinetics and coupling effect between Ni and Co. However, compared with some noble metal-based electrocatalysts, most of them still have problems such as poor conductivity and insufficient intrinsic activity. In addition, many powdered MOF electrocatalysts require binders, which may not only block the active sites, but also make it difficult to assemble and process devices for large-scale industrial applications. Summary of the invention

[0004] In order to solve the technical problem of low catalytic efficiency of catalysts in the prior art, the purpose of the present invention is to provide a highly reconstructed Ni-doped glassy MOFs electrocatalyst and a preparation method and application. The catalyst prepared by this method has more active sites and a high catalytic effect. Moreover, due to its unique melting characteristics, the catalyst can be directly adhered to the electrode material, avoiding the problem that powdered MOFs catalysts are difficult to process.

[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0006] A method for preparing a highly reconstructed Ni-doped glassy MOFs electrocatalyst comprises the following steps:

[0007] A solution containing a cobalt salt and an organic ligand is subjected to a hydrothermal reaction to obtain ZIF-Co powder;

[0008] A mixture of ZIF-Co powder and nickel source was used as a powder precursor;

[0009] Loading a powder precursor onto an electrode material to obtain a catalyst-loaded electrode material;

[0010] The electrode material loaded with the catalyst is vitrified by melt quenching technology to obtain a Ni-doped glassy ZIF-CoNi(g) precatalyst;

[0011] The Ni-doped glassy ZIF-CoNi(g) precatalyst was reconstructed to obtain a highly reconstructed Ni-doped glassy MOFs electrocatalyst.

[0012] The present invention is further improved in that the cobalt salt is cobalt nitrate, the organic ligand is a mixture of imidazole and benzimidazole, the solvent in the solution is N,N-dimethylformamide, the nickel source is nickel acetylacetonate; and the electrode material is foamed copper, foamed nickel or carbon cloth.

[0013] A further improvement of the present invention is that the mass ratio of ZIF-Co powder to nickel acetylacetonate is 4:1-16:1.

[0014] The present invention is further improved in that the molar ratio of imidazole to benzimidazole is 5:1-8:1; the molar ratio of organic ligand to cobalt salt is 2:1-4:1; and the mass ratio of cobalt salt to solvent is 1:60-1:120.

[0015] A further improvement of the present invention is that the temperature of the hydrothermal reaction is 120-150° C. and the time is 48-168 hours.

[0016] A further improvement of the present invention is that the powder precursor is loaded onto the electrode material to obtain the catalyst-loaded electrode material, comprising the following steps:

[0017] The electrode material is placed on the inner wall of a ball mill, and a powder precursor is added and ball milled to obtain a catalyst-loaded electrode material.

[0018] A further improvement of the present invention is that the electrode material loaded with the catalyst is vitrified by melt quenching technology to obtain a Ni-doped glassy ZIF-CoNi(g) precatalyst, comprising the following steps:

[0019] The catalyst-loaded electrode material is placed in an argon or nitrogen inert gas atmosphere, heated to 455-485°C at a heating rate of 8-15°C / min, maintained for 10-30 minutes, and then cooled at a cooling rate of 5-10°C / min to obtain a Ni-doped glassy ZIF-CoNi(g) precatalyst.

[0020] A further improvement of the present invention is that the Ni-doped glassy ZIF-CoNi(g) precatalyst is reconstructed to obtain a highly reconstructed Ni-doped glassy MOFs electrocatalyst, comprising the following steps:

[0021] The Ni-doped glassy ZIF-CoNi(g) precatalyst was subjected to multiple cyclic CV scans in a three-electrode system at a standard hydrogen electrode potential of 1.0 to 1.8 V to obtain a highly reconstructed Ni-doped glassy MOFs electrocatalyst.

[0022] A highly reconfigured Ni-doped glassy MOFs electrocatalyst.

[0023] A highly reconstructed Ni-doped glassy MOFs electrocatalyst for electrooxidation of 5-hydroxymethylfurfural.

[0024] Compared with the existing technology, the present invention has the following beneficial effects:

[0025] The present invention introduces Ni into ZIF-Co for the first time to construct a new glass MOFs catalyst. The catalyst has glassy properties and contains Ni metal particles, which have more active sites and are beneficial to electrocatalytic reactions. The present invention adopts the strategy of vitrification to promote the electrochemical reconstruction process. Since the glassy ZIF-CoNi(g) has stronger charge transfer ability and weaker Co-N connection bonds, the pre-catalyst is deeply reconstructed and has abundant active sites, thus having excellent HMF electro-oxidation performance. The preparation method of a highly reconstructed Ni-doped glassy MOF electrocatalyst proposed in the present invention has simple equipment, mild reaction conditions, low cost, easy process control, no need to add toxic and harmful reagents, and is convenient for the industrialization and engineering application of the catalyst.

[0026] Furthermore, the vitrification process in the present invention is an important factor in determining the performance of the catalyst. This process is achieved through melt quenching technology, in order to induce the Co-N bond to present a disordered state and weaken its bond energy, which is conducive to the subsequent electrochemical reconstruction. Therefore, precise control of the heating temperature and the rate of heating and cooling becomes an indispensable element for optimizing the vitrification effect and thus improving the performance of the catalyst.

[0027] Furthermore, the amount of Ni doping has a significant effect on the performance of the catalyst. The addition of an appropriate amount of Ni can effectively increase the number of active sites, thereby enhancing the catalytic activity. However, when Ni is excessively doped, not only can the catalytic performance not be further improved, but it may interfere with the original Co active sites, resulting in a decrease in performance. Therefore, optimizing the ratio between Co and Ni atoms is the key to improving the overall performance of the catalyst.

[0028] The glassy electrocatalyst prepared by the present invention is melt-adhered to the surface of the electrode material, with full contact, no need for additional adhesive, and will not cover the reaction active sites. At the same time, rapid charge transfer is achieved, solving the problem of difficult processing of powdered MOFs catalysts. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creativity and labor.

[0030] Figure 1 The schematic diagram of the preparation principle of R-ZIF-CoNi(g) provided by the present invention;

[0031] Figure 2 This is a scanning electron microscope image of ZIF-Co obtained in Comparative Example 1 of the present invention;

[0032] Figure 3 is a scanning electron microscope image of ZIF-Co(g) obtained in Comparative Example 1 of the present invention;

[0033] Figure 4 This is a scanning electron microscope image of R-ZIF-Co(g) obtained in Comparative Example 1 of the present invention;

[0034] Figure 5 The ZIF-CoNi obtained in Example 2 of the present invention 0.1 SEM images of the samples; (a) is at a small magnification, and (b) is at a large magnification;

[0035] Figure 6 The ZIF-CoNi obtained in Example 2 of the present invention 0.1 (g) SEM image; (a) is a small magnification, and (b) is a large magnification;

[0036] Figure 7 The R-ZIF-CoNi obtained in Example 2 of the present invention 0.1 (g) SEM image;

[0037] Figure 8 is the X-ray diffraction pattern of the catalyst obtained in Example 2 of the present invention;

[0038] Fig. 9 Cyclic voltammetry curves of the catalysts obtained in Example 2 and Comparative Example 2 of the present invention;

[0039] Fig.10 Linear sweep voltammetry curves of the catalysts obtained in Examples 1-3 and Comparative Examples 1-2 of the present invention;

[0040] Fig.11 The R-ZIF-CoNi obtained in Example 2 of the present invention 0.1 (g) Current-time diagram of the catalyst electrolysis process of HMF;

[0041] Fig.12 The R-ZIF-CoNi obtained in Example 2 and Comparative Example 2 of the present invention 0.1 (g), R-ZIF-CoNi 0.1 The conversion rate (con.) of HMF, the yield (yield) of FDCA and the Faraday efficiency (FE) of FDCA after the electrolysis of HMF by catalyst;

[0042] Fig.13 The R-ZIF-CoNi obtained in Example 2 of the present invention 0.1 (g) Cyclic stability diagram of the HMF electrooxidation of the catalyst with respect to the conversion of the reactant HMF, the yield of FDCA, and the Faradaic efficiency of FDCA. DETAILED DESCRIPTION

[0043] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly and comprehensively understood.

[0044] As an emerging material, glassy MOFs have high porosity, excellent ionic conductivity and charge transfer ability, and therefore have attracted increasing attention. In addition, recent studies have shown that many MOFs electrocatalysts undergo surface reconstruction under electro-oxidation conditions to form actual active sites, thereby exhibiting excellent catalytic performance. Therefore, glassy MOFs are expected to be used as efficient catalysts for HMF electro-oxidation, and the disordered amorphous structure may be conducive to surface reconstruction to form rich active species.

[0045] The present invention solves the technical defects of existing catalysts such as low catalytic efficiency, insufficient active sites, low electron transfer efficiency, difficult processing in powder state, and the need for binders by providing a method for preparing a highly reconstructed Ni-doped glassy MOFs electrocatalyst and its application in HMF electrooxidation. The highly reconstructed Ni-doped glassy MOFs electrocatalyst prepared by the present invention has abundant active sites and excellent catalytic activity, and can also be directly melt-loaded on the surface of electrode materials, and has the potential for industrial application.

[0046] A method for preparing a highly reconstructed Ni-doped glassy MOFs electrocatalyst of the present invention comprises the following steps:

[0047] Add metal salt (cobalt nitrate) and organic ligand (a mixture of imidazole and benzimidazole) to N,N-dimethylformamide solvent and stir for 30-80 minutes, according to the molar ratio of imidazole to benzimidazole of 5:1-8:1, the molar ratio of organic ligand to metal salt of 2:1-4:1, and the mass ratio of metal salt to N,N-dimethylformamide of 1:60-1:120; transfer the mixture to a high-pressure reactor, heat at 120-150°C for 48-168h, wash the product with N,N-dimethylformamide or methanol for 3-5 times, centrifuge and dry to obtain ZIF-Co powder;

[0048] The ZIF-Co powder and nickel acetylacetonate are mixed and ground evenly in a mortar at a mass ratio of 4:1-16:1 to obtain a powder precursor ZIF-CoNi;

[0049] The cleaned electrode material (foam copper, foam nickel or carbon cloth) is selected, cut to size and attached to the inner wall of the ball mill, and zirconium oxide ball milling beads with diameters of 1.2 mm and 3.2 mm, respectively, are used, with masses of 2-6 g and 16-20 g, respectively, and 50-100 g of powder precursor powder, and the powder catalyst is loaded by ball milling at a speed of 350-450 rpm for 5 min to obtain an electrode material loaded with a good catalyst, and the electrode material loaded with a good catalyst is placed in a tubular furnace in an argon or nitrogen inert gas atmosphere, and the temperature is rapidly increased to 455-485° C. at a heating rate of 8-15° C. / min to melt it, and after maintaining it for 10-30 min, it is rapidly cooled at a cooling rate of 5-10° C. / min to vitrify it, and a Ni-doped glassy ZIF-CoNi(g) precatalyst is obtained;

[0050] The Ni-doped glassy ZIF-CoNi(g) precatalyst was electrochemically reconstructed by multiple cyclic CV scans in a three-electrode system. Specifically, the precatalyst was reconstructed by cyclic voltammetry, and the scanning parameters were set as follows: 100-200 cycles at a scan rate of 100 mV / s at a standard hydrogen electrode potential of 1.0-1.8 V to obtain a highly reconstructed Ni-doped glassy MOFs electrocatalyst, namely, R-ZIF-CoNi(g) electrocatalyst.

[0051] A highly reconstructed Ni-doped glassy MOFs electrocatalyst is prepared according to the method described above.

[0052] A highly reconstructed Ni-doped glassy MOFs electrocatalyst as described above was used for the electrooxidation of 5-hydroxymethylfurfural (HMF).

[0053] Figure 1 This is a schematic diagram of the preparation principle of the R-ZIF-CoNi(g) electrocatalyst provided by the present invention. Figure 1 The precursors of ZIF-62(Co)(ZIF-Co) and nickel acetylacetonate (Ni(acac)2) were first fully ground and mixed, and then glassy ZIF-CoNi (ZIF-CoNi(g)) was plated on copper foam (CF) by a two-step method of ball milling and melt quenching. Subsequently, it was reconstructed by cyclic voltammetry (CV) to obtain the electrochemically reconstructed ZIF-CoNi(g), namely R-ZIF-CoNi(g) electrocatalyst.

[0054] The HMF electro-oxidation performance of the following Examples 1-3 and Comparative Examples 1-2 was tested in a typical H-type electrolytic cell three-electrode system, using the prepared conductive substrates (0.9×0.9 cm 2) Directly used as the working electrode, carbon rod as the counter electrode, Hg / HgO as the reference electrode, the electrolyte solution is 1.0 mol / L KOH containing 10 mmol / L HMF. The potential in the test can be converted into the reversible hydrogen electrode potential E (RHE) by the Stirling equation. The following HMF electrolysis product analysis tests of Examples 1-3 and Comparative Examples 1-2 were performed at a voltage of 1.48 V vs. RHE for a long time. The electrolyte was 30 mL of a 1.0 mol / L KOH solution containing 10 mmol / L HMF, and the sample solution was taken at the anode end at regular intervals for analysis using high performance liquid chromatography.

[0055] The present invention is further described by the following examples, and the present invention can be better understood according to the following examples. However, it is easy for those skilled in the art to understand that the specific material ratios, process conditions and results described in the examples are only used to illustrate the present invention, and should not and will not limit the present invention described in detail in the claims.

[0056] Example 1

[0057] Step 1), 4mmol cobalt nitrate, 11.6mmol imidazole and 1.6mmol benzimidazole were added to 90mL N,N-dimethylformamide solvent and stirred for 60min, the mixture was transferred to a high pressure reactor, heated at 130°C for 168h, the product was washed 3 times with N,N-dimethylformamide, centrifuged, and vacuum dried at 70°C for 12h to obtain ZIF-Co powder;

[0058] Step 2), ZIF-Co and nickel acetylacetonate were mixed and ground evenly in a mass ratio of 16:1 to obtain ZIF-CoNi 0.05 ;

[0059] Step 3), select the cleaned foam copper, cut it to size and stick it to the inner wall of the ball mill, use zirconia ball milling beads with diameters of 1.2 mm and 3.2 mm, with masses of 4 g and 18 g respectively, and 60 g of catalyst powder, and ball mill for 5 min at a speed of 400 rpm to load the powder catalyst, and place the electrode material loaded with the catalyst in a tubular furnace in an argon atmosphere, and rapidly heat it to 470 ° C at a heating rate of 10 ° C / min to melt it, keep it for 20 minutes, and then rapidly cool it at a cooling rate of 10 ° C / min to vitrify it, and obtain Ni-doped glassy ZIF-CoNi 0.05 (g) a precatalyst;

[0060] Step 4) In a three-electrode system, the pre-catalyst was reconstructed by cyclic voltammetry, the parameters were set to 1.0-1.8 V, and the scan rate was 100 mV / s for 100 cycles to obtain a reconstructed glassy catalyst, which was recorded as R-ZIF-CoNi 0.05 (g).

[0061] from Fig.10 The LSV curve of R-ZIF-CoNi 0.05 (g) shows good HMF electrooxidation performance at 10 mA cm -2 The potential only needs to be 1.365V vs. RHE at a current density of . Compared with Comparative Example 1, the potential of the electrocatalyst is reduced, which indicates that doping Ni can effectively promote the reaction.

[0062] Example 2

[0063] Step 1), 4mmol cobalt nitrate, 11.6mmol imidazole and 1.6mmol benzimidazole were added to 90mL N,N-dimethylformamide solvent and stirred for 60min, the mixture was transferred to a high pressure reactor, heated at 130°C for 168h, the product was washed 3 times with N,N-dimethylformamide, centrifuged, and vacuum dried at 70°C for 12h to obtain ZIF-Co powder;

[0064] Step 2), ZIF-Co and nickel acetylacetonate were mixed and ground evenly in a mass ratio of 8:1 to obtain ZIF-CoNi 0.1 ;

[0065] Step 3), select the cleaned foam copper, cut it to size and stick it to the inner wall of the ball mill, use zirconia ball milling beads with diameters of 1.2 mm and 3.2 mm, with masses of 4 g and 18 g respectively, and 60 g of catalyst powder, and ball mill for 5 min at a speed of 400 rpm to load the powder catalyst, and place the electrode material loaded with the catalyst in a tubular furnace in an argon atmosphere, and rapidly heat it to 470 ° C at a heating rate of 10 ° C / min to melt it, keep it for 20 minutes, and then rapidly cool it at a cooling rate of 10 ° C / min to vitrify it, and obtain Ni-doped glassy ZIF-CoNi 0.1 (g) a precatalyst;

[0066] Step 4) In a three-electrode system, the pre-catalyst was reconstructed by cyclic voltammetry, the parameters were set to 1.0-1.8 V, and the scan rate was 100 mV / s for 100 cycles to obtain a reconstructed glassy catalyst, which was recorded as R-ZIF-CoNi 0.1 (g).

[0067] Figure 5 (a) and (b) are ZIF-CoNi of this embodiment. 0.1 From the scanning electron microscope image, we can clearly see that the catalyst particles are loaded on the copper foam.

[0068] Figure 6 (a) and (b) are ZIF-CoNi of this embodiment. 0.1 (g) The scanning electron microscope image clearly shows that the catalyst is molten and loaded on the copper foam.

[0069] Figure 7 R-ZIF-CoNi in this embodiment 0.1 The scanning electron microscopy image of (g) clearly shows that more lamellar structures appear on the surface after reconstruction, forming new active centers.

[0070] Figure 8 is the X-ray diffraction (XRD) pattern of the catalyst in this example, ZIF-CoNi 0.1 Crystal structure; ZIF-CoNi0.1 (g) It is amorphous and has a long-range disordered glassy structure.

[0071] from Fig.10 The LSV curve of R-ZIF-CoNi0 .1 (g) shows good HMF electrooxidation performance at 10 mA cm -2 The potential only needs to be 1.36 V vs. RHE at a current density of . Compared with Example 1, the potential of the electrocatalyst is further reduced, which indicates that increasing the amount of Ni doping will improve the catalytic activity.

[0072] Example 3

[0073] Step 1), 4mmol cobalt nitrate, 11.6mmol imidazole and 1.6mmol benzimidazole were added to 90mL N,N-dimethylformamide solvent and stirred for 60min, the mixture was transferred to a high pressure reactor, heated at 130°C for 168h, the product was washed 3 times with N,N-dimethylformamide, centrifuged, and vacuum dried at 70°C for 12h to obtain ZIF-Co powder;

[0074] Step 2), ZIF-Co and nickel acetylacetonate were mixed and ground evenly in a mass ratio of 16:3 to obtain ZIF-CoNi 0.15 ;

[0075] Step 3), select the cleaned foam copper, cut it to size and stick it to the inner wall of the ball mill, use zirconia ball milling beads with diameters of 1.2 mm and 3.2 mm, with masses of 4 g and 18 g respectively, and 60 g of catalyst powder, and ball mill for 5 min at a speed of 400 rpm to load the powder catalyst, and place the electrode material loaded with the catalyst in a tubular furnace in an argon atmosphere, and rapidly heat it to 470 ° C at a heating rate of 10 ° C / min to melt it, keep it for 20 minutes, and then rapidly cool it at a cooling rate of 10 ° C / min to vitrify it, and obtain Ni-doped glassy ZIF-CoNi 0.15 (g) a precatalyst;

[0076] Step 4) In a three-electrode system, the pre-catalyst was reconstructed by cyclic voltammetry, the parameters were set to 1.0-1.8 V, and the scan rate was 100 mV / s for 100 cycles to obtain a reconstructed glassy catalyst, which was recorded as R-ZIF-CoNi 0.15 (g).

[0077] from Fig.10 The LSV curve of R-ZIF-CoNi 0.15 (g) shows good HMF electrooxidation performance at 10 mA cm -2The potential only needs to be 1.36 V vs. RHE at a current density of . Compared with Example 2, the potential of the electrocatalyst does not change, which indicates that further increasing the amount of doped Ni does not contribute to the catalytic activity.

[0078] Comparative Example 1

[0079] Step 1), 4mmol cobalt nitrate, 11.6mmol imidazole and 1.6mmol benzimidazole were added to 90mL N,N-dimethylformamide solvent and stirred for 60min, the mixture was transferred to a high pressure reactor, heated at 130°C for 168h, the product was washed 3 times with N,N-dimethylformamide, centrifuged, and vacuum dried at 70°C for 12h to obtain ZIF-Co powder;

[0080] Step 2), select the cleaned foam copper, cut it to size and stick it to the inner wall of the ball mill, use zirconia ball milling beads with diameters of 1.2 mm and 3.2 mm, with masses of 4 g and 18 g respectively, and 60 g of catalyst powder, and ball mill for 5 min at a speed of 400 rpm to load the powder catalyst, and place the electrode material loaded with the catalyst in a tubular furnace in an argon atmosphere, and rapidly heat it to 470 ° C at a heating rate of 10 ° C / min to melt it, keep it for 20 minutes, and then rapidly cool it at a cooling rate of 10 ° C / min to vitrify it, and obtain a glassy ZIF-Co (g) precatalyst;

[0081] Step 3) In a three-electrode system, the pre-catalyst was reconstructed by cyclic voltammetry with the parameters set to 1.0-1.8 V and a scan rate of 100 mV / s for 100 cycles to obtain a reconstructed glassy electrocatalyst, which was recorded as R-ZIF-Co(g).

[0082] The structural formula of the MOF of the glassy electrocatalyst of this comparative example is ZIF-62(Co)[Co(Im) 1.75 (bIm) 0.25 ], the melting point of the catalyst is 425 ° C, and the glass transition temperature is 365 ° C. Compared with the crystalline state, glassy MOFs have disordered and weak Co-N bonds, which are more prone to reconstruction. The reconstructed R-ZIF-Co(g) has abundant active sites.

[0083] Figure 2 The scanning electron microscope image of ZIF-Co in this comparative example clearly shows that the catalyst particles are loaded on the copper foam.

[0084] Figure 3 The scanning electron microscope image of ZIF-Co(g) of this comparative example clearly shows that the catalyst is molten and loaded on the copper foam.

[0085] Figure 4The scanning electron microscope image of R-ZIF-Co(g) in this comparative example clearly shows that a lamellar structure appears on the surface after reconstruction, forming a new active center.

[0086] Fig.10 The corresponding linear sweep voltammetry (LSV) curve is shown in Figure 2. At a current density of 10 mA cm -2 At , the potential of the R-ZIF-Co(g) electrocatalyst was 1.380 V vs. RHE, showing good HMF electro-oxidation performance.

[0087] Comparative Example 2

[0088] Step 1), 4mmol cobalt nitrate, 11.6mmol imidazole and 1.6mmol benzimidazole were added to 90mL N,N-dimethylformamide solvent and stirred for 60min, the mixture was transferred to a high pressure reactor, heated at 130°C for 168h, the product was washed 3 times with N,N-dimethylformamide, centrifuged, and vacuum dried at 70°C for 12h to obtain ZIF-Co powder;

[0089] Step 2), ZIF-Co and nickel acetylacetonate were mixed and ground evenly in a mass ratio of 8:1 to obtain ZIF-CoNi 0.1 ;

[0090] Step 3), select the cleaned foam copper, cut it to size and stick it to the inner wall of the ball mill, use zirconia ball milling beads with diameters of 1.2 mm and 3.2 mm, with masses of 4 g and 18 g respectively, and 60 g of catalyst powder, and ball mill at a speed of 400 rpm for 5 min to load the powdered catalyst;

[0091] Step 4) In a three-electrode system, the pre-catalyst was reconstructed by cyclic voltammetry, the parameters were set to 1.0-1.8 V, and the scan rate was 100 mV / s for 100 cycles to obtain the reconstructed catalyst, which was recorded as R-ZIF-CoNi 0.1 .

[0092] Fig. 9 The cyclic voltammetry curves of the catalysts in Example 2 and Comparative Example 2 are shown in Table 2. 0.1 and ZIF-CoNi 0.1 The curves of (g) show a significant rise, which is attributed to the dynamic electrochemical reconstruction process. 0.1 Compared with ZIF-CoNi 0.1 (g) After 100 cycles, it exhibits a stronger oxidation peak and higher current density, which indicates that vitrification promotes surface reconstruction.

[0093] from Fig.10The LSV curve of R-ZIF-CoNi 0.1 Catalyst at 10 mA cm -2 The potential at the current density of 1.4 V vs. RHE is required. The potential of the electrocatalyst is significantly higher than that of Examples 1 to 3 and Comparative Example 1, which indicates that vitrification is an important factor affecting catalytic activity. Vitrification can promote the reconstruction process to produce more active centers, which is beneficial to the HMF reaction.

[0094] Fig.11 The current-time diagram of the HMF electrolysis process shows that the R-ZIF-CoNi prepared in Example 2 of the present invention 0.1 The electrolysis time of the HMF electro-oxidation process (g) is only 160 min, which has excellent reaction performance.

[0095] Fig.12 The HMF conversion rate, FDCA yield and FDCA Faraday efficiency diagram of the HMF electrolysis process, R-ZIF-CoNi prepared in Example 2 of the present invention and Comparative Example 2 0.1 (g) and R-ZIF-CoNi 0.1 The final HMF conversions were 100% and 93%, the FDCA yields were 99.6% and 91.3%, and the FDCA Faraday efficiencies were 98.5% and 90.1%, respectively. This shows that the vitrified catalyst can provide more catalytic active sites and exhibit excellent performance.

[0096] Fig.13 R-ZIF-CoNi prepared in Example 2 of the present invention 0.1 (g) After seven cycles of HMF electrooxidation catalysis, there was no obvious decay in HMF conversion, FDCA yield, and FDCA Faradaic efficiency, demonstrating excellent catalytic cycle stability.

[0097] Example 4

[0098] Step 1), add 4mmol cobalt nitrate, imidazole and benzimidazole to N,N-dimethylformamide solvent and stir for 30min, transfer the mixture to a high pressure reactor, heat at 150°C for 48h, wash the product with N,N-dimethylformamide three times, centrifuge, and vacuum dry at 70°C for 12h to obtain ZIF-Co powder; wherein the molar ratio of imidazole to benzimidazole is 5:1, the molar ratio of the total amount of imidazole and benzimidazole to cobalt nitrate is 4:1, and the mass ratio of cobalt nitrate to N,N-dimethylformamide is 1:60.

[0099] Step 2), ZIF-Co and nickel acetylacetonate are mixed and ground evenly in a mass ratio of 5:1 to obtain ZIF-CoNi;

[0100] Step 3), select the cleaned foam copper, cut it to size and stick it to the inner wall of the ball mill, use zirconia ball milling beads with diameters of 1.2 mm and 3.2 mm, with masses of 2 g and 18 g respectively, and 50 g of catalyst powder, and ball mill at a speed of 400 rpm for 5 min to load the powder catalyst, and place the electrode material loaded with the catalyst in a tubular furnace in an argon atmosphere, and rapidly heat it to 465 ° C at a heating rate of 8 ° C / min to melt it, keep it for 20 minutes, and then rapidly cool it at a cooling rate of 8 ° C / min to vitrify it, and obtain a Ni-doped glassy ZIF-CoNi (g) precatalyst;

[0101] Step 4), in a three-electrode system, the pre-catalyst was reconstructed by cyclic voltammetry, the parameters were set to 1.0-1.8 V, and the scan rate was 100 mV / s for 150 cycles to obtain the R-ZIF-CoNi(g) electrocatalyst.

[0102] Example 5

[0103] Step 1), add 4mmol cobalt nitrate, imidazole and benzimidazole to N,N-dimethylformamide solvent and stir for 40min, transfer the mixture to a high pressure reactor, heat at 140°C for 72h, wash the product with N,N-dimethylformamide three times, centrifuge, and vacuum dry at 70°C for 12h to obtain ZIF-Co powder; wherein the molar ratio of imidazole to benzimidazole is 8:1, the molar ratio of the total amount of imidazole and benzimidazole to cobalt nitrate is 7:2, and the mass ratio of cobalt nitrate to N,N-dimethylformamide is 1:100.

[0104] Step 2), ZIF-Co and nickel acetylacetonate are mixed and ground evenly in a mass ratio of 7:1 to obtain ZIF-CoNi;

[0105] Step 3), select the cleaned foam copper, cut it to size and stick it to the inner wall of the ball mill, use zirconia ball milling beads with diameters of 1.2 mm and 3.2 mm, with masses of 3 g and 17 g respectively, and 100 g of catalyst powder, and ball mill at a speed of 420 rpm for 5 min to load the powder catalyst, and place the electrode material loaded with the catalyst in a tubular furnace in an argon atmosphere, and rapidly heat it to 480 ° C at a heating rate of 18 ° C / min to melt it, keep it for 15 minutes, and then rapidly cool it at a cooling rate of 15 ° C / min to vitrify it, and obtain a Ni-doped glassy ZIF-CoNi (g) precatalyst;

[0106] Step 4), in a three-electrode system, the pre-catalyst was reconstructed by cyclic voltammetry, the parameters were set to 1.0-1.8 V, and the scan rate was 100 mV / s for 200 cycles until it was stable, to obtain the R-ZIF-CoNi(g) electrocatalyst.

[0107] Example 6

[0108] Step 1), 4mmol of cobalt nitrate, imidazole and benzimidazole are added to N,N-dimethylformamide solvent and stirred for 60min, the mixture is transferred to a high-pressure reactor, heated at 130°C for 120h, the product is washed 3 times with N,N-dimethylformamide, centrifuged, and vacuum dried at 70°C for 12h to obtain ZIF-Co powder; wherein the molar ratio of imidazole to benzimidazole is 6:1, the molar ratio of the total amount of imidazole and benzimidazole to cobalt nitrate is 5:2, and the mass ratio of cobalt nitrate to N,N-dimethylformamide is 1:70.

[0109] Step 2), ZIF-Co and nickel acetylacetonate are mixed and ground evenly in a mass ratio of 13:1 to obtain ZIF-CoNi;

[0110] Step 3), select the cleaned foam copper, cut it to size and stick it to the inner wall of the ball mill, use zirconia ball milling beads with diameters of 1.2 mm and 3.2 mm, with masses of 4 g and 18 g respectively, and 70 g of catalyst powder, and ball mill at a speed of 370 rpm for 5 min to load the powder catalyst, place the electrode material loaded with the catalyst in a tubular furnace in an argon atmosphere, and rapidly heat it to 470 ° C at a heating rate of 12 ° C / min to melt it, keep it for 20 minutes, and then rapidly cool it at a cooling rate of 12 ° C / min to vitrify it, and obtain a Ni-doped glassy ZIF-CoNi (g) precatalyst;

[0111] Step 4), in a three-electrode system, the pre-catalyst was reconstructed by cyclic voltammetry, the parameters were set to 1.0-1.8 V, and the scan rate was 100 mV / s for 120 cycles to obtain the R-ZIF-CoNi(g) electrocatalyst.

[0112] Example 7

[0113] Step 1), add 4mmol cobalt nitrate, imidazole and benzimidazole to N,N-dimethylformamide solvent and stir for 70min, transfer the mixture to a high pressure reactor, heat at 120°C for 140h, wash the product with N,N-dimethylformamide 3 times, centrifuge, and vacuum dry at 70°C for 12h to obtain ZIF-Co powder; wherein the molar ratio of imidazole to benzimidazole is 7:1, the molar ratio of the total amount of imidazole and benzimidazole to cobalt nitrate is 7:2, and the mass ratio of cobalt nitrate to N,N-dimethylformamide is 1:80.

[0114] Step 2), ZIF-Co and nickel acetylacetonate are mixed and ground evenly in a mass ratio of 12:1 to obtain ZIF-CoNi;

[0115] Step 3), select the cleaned foam copper, cut it to size and stick it to the inner wall of the ball mill, use zirconia ball milling beads with diameters of 1.2 mm and 3.2 mm, with masses of 5 g and 16 g respectively, and 90 g of catalyst powder, and ball mill for 5 min at a speed of 400 rpm to load the powder catalyst, and place the electrode material loaded with the catalyst in a tubular furnace in an argon atmosphere, and rapidly heat it to 460 ° C at a heating rate of 13 ° C / min to melt it, keep it for 30 minutes, and then rapidly cool it at a cooling rate of 13 ° C / min to vitrify it, and obtain a Ni-doped glassy ZIF-CoNi (g) precatalyst;

[0116] Step 4), in a three-electrode system, the pre-catalyst was reconstructed by cyclic voltammetry, the parameters were set to 1.0-1.8 V, and the scan rate was 100 mV / s for 180 cycles to obtain the R-ZIF-CoNi(g) electrocatalyst.

[0117] Example 8

[0118] Step 1), add 4mmol cobalt nitrate, imidazole and benzimidazole to N,N-dimethylformamide solvent and stir for 80min, transfer the mixture to a high pressure reactor, heat at 120°C for 168h, wash the product with N,N-dimethylformamide 5 times, centrifuge, and vacuum dry at 70°C for 12h to obtain ZIF-Co powder; wherein the molar ratio of imidazole to benzimidazole is 8:1, the molar ratio of the total amount of imidazole and benzimidazole to cobalt nitrate is 3:1, and the mass ratio of cobalt nitrate to N,N-dimethylformamide is 1:120.

[0119] Step 2), ZIF-Co and nickel acetylacetonate were mixed and ground evenly in a mass ratio of 4:1 to obtain ZIF-CoNi 0.2 ;

[0120] Step 3), select the cleaned foam copper, cut it to size and stick it to the inner wall of the ball mill, use zirconia ball milling beads with diameters of 1.2 mm and 3.2 mm, with masses of 6 g and 19 g respectively, and 80 g of catalyst powder, and ball mill at a speed of 450 rpm for 5 min to load the powder catalyst, and place the electrode material loaded with the catalyst in a tubular furnace in an argon atmosphere, and rapidly heat it to 485 ° C at a heating rate of 14 ° C / min to melt it, keep it for 10 minutes, and then rapidly cool it at a cooling rate of 14 ° C / min to vitrify it, and obtain Ni-doped glassy ZIF-CoNi 0.2 (g) a precatalyst;

[0121] Step 4) In a three-electrode system, the pre-catalyst was reconstructed by cyclic voltammetry, the parameters were set to 1.0-1.8 V, and the scan rate was 100 mV / s for 170 cycles to obtain R-ZIF-CoNi 0.2 (g) Electrocatalyst.

[0122] Example 9

[0123] Step 1), add 4mmol cobalt nitrate, imidazole and benzimidazole to N,N-dimethylformamide solvent and stir for 50min, transfer the mixture to a high pressure reactor, heat at 135°C for 96h, wash the product with N,N-dimethylformamide 4 times, centrifuge, and vacuum dry at 70°C for 12h to obtain ZIF-Co powder; wherein the molar ratio of imidazole to benzimidazole is 5:1, the molar ratio of the total amount of imidazole and benzimidazole to cobalt nitrate is 2:1, and the mass ratio of cobalt nitrate to N,N-dimethylformamide is 1:120.

[0124] Step 2), ZIF-Co and nickel acetylacetonate are mixed and ground evenly in a mass ratio of 8:1 to obtain ZIF-CoNi;

[0125] Step 3), select the cleaned foam copper, cut it to size and stick it to the inner wall of the ball mill, use zirconia ball milling beads with diameters of 1.2 mm and 3.2 mm, with masses of 4 g and 20 g respectively, and 70 g of catalyst powder, and ball mill the loaded powder catalyst at a speed of 350 rpm for 5 min, place the electrode material loaded with the catalyst in a tubular furnace in an argon atmosphere, and rapidly heat it to 455 ° C at a heating rate of 11 ° C / min to melt it, keep it for 30 minutes, and then rapidly cool it at a cooling rate of 11 ° C / min to vitrify it, and obtain a Ni-doped glassy ZIF-CoNi (g) precatalyst;

[0126] Step 4), in a three-electrode system, the pre-catalyst was reconstructed by cyclic voltammetry, the parameters were set to 1.0-1.8 V, and the scan rate was 100 mV / s for 130 cycles to obtain the R-ZIF-CoNi(g) electrocatalyst.

[0127] In the present invention, the vitrification process is an important factor in determining the performance of the catalyst. This process is achieved by melt quenching technology, in order to induce the Co-N bond to present a disordered state and weaken its bond energy, which is conducive to the occurrence of subsequent electrochemical reconstruction. Therefore, accurately controlling the heating temperature and the rate of heating and cooling becomes an indispensable element for optimizing the vitrification effect and thus improving the performance of the catalyst. In addition, the amount of Ni doping has a significant effect on the performance of the catalyst, and the addition of an appropriate amount of Ni can effectively increase the number of active sites, thereby enhancing the catalytic activity. However, when Ni is excessively doped, not only can the catalytic performance not be further improved, but it may interfere with the original Co active sites, resulting in performance degradation. Therefore, optimizing the ratio between Co and Ni atoms is the key to improving the overall performance of the catalyst.

[0128] The present invention utilizes vitrification to promote electrochemical surface reconstruction, thereby obtaining a glassy MOFs catalyst with abundant active sites, solving the problem that the active sites of MOFs materials are not easily exposed. In addition, glassy MOFs can be directly melt-attached to electrode materials without the need for binders, solving the problem that powder catalysts are difficult to process and facilitating device assembly and industrial-scale production.

[0129] The above description is only for the best embodiment of the present invention, but it should not be understood as limiting the claims. The present invention is not limited to the above embodiments, and its specific structure is allowed to be changed. However, all changes made within the protection scope of the independent claims of the present invention are within the protection scope of the present invention.

[0130] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

Claims

1. A method for preparing a highly reconstructed Ni-doped glassy MOFs electrocatalyst, characterized in that: The following steps are involved: A solution containing a cobalt salt and an organic ligand is subjected to a hydrothermal reaction to obtain ZIF-Co powder; A mixture of ZIF-Co powder and nickel source was used as a powder precursor; Loading a powder precursor onto an electrode material to obtain a catalyst-loaded electrode material; The electrode material loaded with the catalyst is vitrified by melt quenching technology to obtain a Ni-doped glassy ZIF-CoNi(g) precatalyst; The Ni-doped glassy ZIF-CoNi(g) precatalyst was reconstructed to obtain a highly reconstructed Ni-doped glassy MOFs electrocatalyst.

2. The method for preparing the highly reconstructed Ni-doped glassy MOFs electrocatalyst according to claim 1, characterized in that: The cobalt salt is cobalt nitrate, the organic ligand is a mixture of imidazole and benzimidazole, the solvent in the solution is N,N-dimethylformamide, the nickel source is nickel acetylacetonate; and the electrode material is foamed copper, foamed nickel or carbon cloth.

3. The method for preparing the highly reconstructed Ni-doped glassy MOFs electrocatalyst according to claim 2, characterized in that: The mass ratio of ZIF-Co powder to nickel acetylacetonate is 4:1-16:

1.

4. The method for preparing the highly reconstructed Ni-doped glassy MOFs electrocatalyst according to claim 1, characterized in that: The molar ratio of imidazole to benzimidazole is 5:1-8:1; the molar ratio of organic ligand to cobalt salt is 2:1-4:1; and the mass ratio of cobalt salt to solvent is 1:60-1:

120.

5. The method for preparing the highly reconstructed Ni-doped glassy MOFs electrocatalyst according to claim 1, characterized in that: The temperature of the hydrothermal reaction is 120-150°C and the time is 48-168h.

6. The method for preparing the highly reconstructed Ni-doped glassy MOFs electrocatalyst according to claim 1, characterized in that: Loading the powder precursor onto the electrode material to obtain a catalyst-loaded electrode material, The following steps are involved: The electrode material is placed on the inner wall of a ball mill, and a powder precursor is added and ball milled to obtain a catalyst-loaded electrode material.

7. The method for preparing a highly reconstructed Ni-doped glassy MOFs electrocatalyst according to claim 1, characterized in that: The electrode material loaded with the catalyst is vitrified by melt quenching technology to obtain a Ni-doped glassy ZIF-CoNi(g) precatalyst, comprising the following steps: The catalyst-loaded electrode material is placed in an argon or nitrogen inert gas atmosphere, heated to 455-485°C at a heating rate of 8-15°C / min, maintained for 10-30 minutes, and then cooled at a cooling rate of 5-10°C / min to obtain a Ni-doped glassy ZIF-CoNi(g) precatalyst.

8. The method for preparing a highly reconstructed Ni-doped glassy MOFs electrocatalyst according to claim 1, characterized in that: The Ni-doped glassy ZIF-CoNi(g) precatalyst is reconstructed to obtain a highly reconstructed Ni-doped glassy MOFs electrocatalyst, comprising the following steps: The Ni-doped glassy ZIF-CoNi(g) precatalyst was subjected to multiple cyclic CV scans in a three-electrode system at a standard hydrogen electrode potential of 1.0 to 1.8 V to obtain a highly reconstructed Ni-doped glassy MOFs electrocatalyst.

9. A highly reconstructed Ni-doped glassy MOFs electrocatalyst prepared according to the method according to any one of claims 1 to 8.

10. Use of a highly reconstructed Ni-doped glassy MOFs electrocatalyst prepared according to the method of any one of claims 1 to 8 in the electro-oxidation of 5-hydroxymethylfurfural.

Citation Information

Patent Citations

  • Nitrogen-doped carbon nanotube coated CoNi nano-alloy catalyst as well as preparation method and application thereof

    CN115478293A

  • Preparation method of vitrified ZIF-300 material

    CN116143414A

  • Monatomic catalyst based on metal organic framework electrochemical reconstruction as well as synthesis method and application of monatomic catalyst

    CN116536694A

  • Preparation method of Fe-based MOFs glass and application of Fe-based MOFs glass in advanced oxidation

    CN117160538A

Cited By

  • Core-shell type bifunctional electrocatalyst with crystalline amorphous interface and preparation method and application of core-shell type bifunctional electrocatalyst

    CN120683555A

  • Glass-state electrocatalyst with rich Co-Sn interface as well as preparation method and application of glass-state electrocatalyst

    CN122382651A